2017
DOI: 10.1002/wsbm.1392
|View full text |Cite
|
Sign up to set email alerts
|

Image‐based computational fluid dynamics in the lung: virtual reality or new clinical practice?

Abstract: The development and implementation of personalized medicine is paramount to improving the efficiency and efficacy of patient care. In the respiratory system, function is largely dictated by the choreographed movement of air and blood to the gas exchange surface. The passage of air begins in the upper airways, either via the mouth or nose, and terminates at the alveolar interface, while blood flows from the heart to the alveoli and back again. Computational fluid dynamics (CFD) is a well-established tool for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 72 publications
(162 reference statements)
0
13
0
Order By: Relevance
“…Computational Fluid Dynamics (CFD) represents an attractive tool to overcome the drawbacks of the current clinical approaches, providing quantitative information on regional ventilation, lobar flow rate, and local properties at every location in the airways. 8 , 13 , 14 , 15 The geometrical model of the airways can be reconstructed from the CT‐images of the patient, 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 allowing to replicate the anatomical peculiarities of a subject and to study the effects of lung pathologies. Burrowes et al modeled the morphological changes due to asthma and chronic obstructive pulmonary disease (COPD), 22 , 23 while De Backer et al showed the fluid dynamic consequences of such pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Computational Fluid Dynamics (CFD) represents an attractive tool to overcome the drawbacks of the current clinical approaches, providing quantitative information on regional ventilation, lobar flow rate, and local properties at every location in the airways. 8 , 13 , 14 , 15 The geometrical model of the airways can be reconstructed from the CT‐images of the patient, 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 allowing to replicate the anatomical peculiarities of a subject and to study the effects of lung pathologies. Burrowes et al modeled the morphological changes due to asthma and chronic obstructive pulmonary disease (COPD), 22 , 23 while De Backer et al showed the fluid dynamic consequences of such pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the individualized structural models of the tracheobronchial tree extracted from CT images, the computational fluid dynamics (CFD) simulation can provide physiologically significant ventilation information including the airflow velocity, wall pressure, wall shear stress, pressure drop and lobular airflow rate, which may complement the results of anatomy and pulmonary function [1417]. Walters et al proposed to use the reduced geometry model to reduce the complexity [18].…”
Section: Introductionmentioning
confidence: 99%
“…Computational Fluid Dynamics (CFD) represents a feasible solution to overcome the drawbacks of the current clinical approaches. From image-based patient-specific bronchial tree reconstructions, CFD can provide quantitative information on regional ventilation and local airflow properties in the bronchial tree 14 17 . CFD has been applied to several pathologies of the lower respiratory tract, such as tracheal stenosis 18 , asthma, chronic obstructive pulmonary disease 19 , 20 , and cystic fibrosis 21 .…”
Section: Introductionmentioning
confidence: 99%